Inhibition of NF-κB improves the stress resistance and myogenic differentiation of MDSPCs isolated from naturally aged mice. - Jonathan D Proto; Aiping Lu; Akaitz Dorronsoro; Alex Scibetta; Paul D Robbins; Laura J Niedernhofer; Johnny Huard (PLoS ONE)
A decline in the regenerative capacity of adult stem cells with aging is well documented. As a result of this decline, the efficacy of autologous stem cell therapies is likely to decline with increasing donor age. In these cases, strategies to restore the function of aged stem cells would have clinical utility. Globally, the transcription factor NF-κB is up-regulated in aged tissues. Given the negative role that NF-κB plays in myogenesis, we investigated whether the age-related decline in the function of muscle-derived stem/progenitor cells (MDSPCs) could be improved by inhibition of NF-κB. Herein, we demonstrate that pharmacologic or genetic inhibition of NF-κB activation increases myogenic differentiation and improves resistance to oxidative stress. Our results suggest that MDSPC "aging" may be reversible, and that pharmacologic targeting of pathways such as NF-κB may enhance the efficacy of cell-based therapies.